2020
DOI: 10.1177/0193945920963130
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Patient Activation: The Role of Economic Diversity

Abstract: The Patient Activation Measure (PAM) assesses a person’s level of knowledge, skills, and confidence to self-manage their day-to-day health. We conducted a mediation analysis to examine potential direct effects of race on significantly lower baseline PAM scores in Black than in White participants (p<0.001) who were a subset of 184 adults who participated in a randomized controlled trial. In the mediation analysis, using natural indirect effects, the continuous outcome was the PAM score. The mediators were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…We found that lower personal monthly income, self-rated method of ART effect based on self-perception and higher illness perception score were associated with a lower PAM score. It is not surprising that lower personal monthly income is a risk factor for a low PAM score, which is consistent with the findings reported in previous studies that the income levels of participants are related to patient activation (29)(30)(31). Participants with a lower income might spend less money and exert less effort on health maintenance (31), resulting in a low PAM score; they may also adopt more passive behavior toward the management of their health.…”
Section: Discussionsupporting
confidence: 88%
“…We found that lower personal monthly income, self-rated method of ART effect based on self-perception and higher illness perception score were associated with a lower PAM score. It is not surprising that lower personal monthly income is a risk factor for a low PAM score, which is consistent with the findings reported in previous studies that the income levels of participants are related to patient activation (29)(30)(31). Participants with a lower income might spend less money and exert less effort on health maintenance (31), resulting in a low PAM score; they may also adopt more passive behavior toward the management of their health.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study among elderly minority patients 39 reported that the relationship between African American race and lower patient activation was fully mediated by health literacy. Another study among patients who attended primary care clinics reported lower activation scores among Black participants but suggested that the relationship between race and activation could be mediated by income 40 . Unfortunately, in our study, we did not collect health literacy and income data to confirm this finding.…”
Section: Discussionmentioning
confidence: 55%
“…Another study among patients who attended primary care clinics reported lower activation scores among Black participants but suggested that the relationship between race and activation could be mediated by income. 40 Unfortunately, in our study, we did not collect health literacy and income data to confirm this finding. Second, when interpreting our results, it is important to consider that even though the PAM has been used across multiple racial, ethnic and language groups, 41 it is unknown if the contextual components of PAM are race or culturally specific.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Patients with higher activation are more likely to have a usual source of care, more likely to get preventive care, less likely to delay getting care ( Hibbard & Cunningham, 2008 ), and have better health outcomes ( Greene & Hibbard, 2012 ). Several studies have found lower patient activation in Black/African American individuals than in White individuals ( Eliacin et al, 2018 , Gwynn et al, 2016 , Hibbard et al, 2008 , Holt et al, 2021 ), leading to consideration of whether targeting improvements in patient activation among racial minorities could lead to reducing disparities in health outcomes.…”
Section: Introductionmentioning
confidence: 99%